Case presentation: ODS in the Faculty of Professional Studies of the National University of Rafaela - Gutiérrez, María Cecilia (2024)
In 2022, the Secretariat of University Policies under Argentina's Ministry of Education launched the "Sustainable Universities" initiative, aimed at raising awareness and institutionalizing efforts to promote the Sustainable Development Goals (SDGs) within universities. Universidad Nacional de Rafaela (UNRaf) participated with a project led by the Faculty of Professional Studies, focusing on integrating SDGs into the university’s strategic planning. The initial phase involved training key university staff on SDG implementation, leading to the identification of ten priority SDGs and aligning programs with these goals. By 2023, a report revealed that most actions concentrated on SDGs 4 (Quality Education), 9 (Industry, Innovation, and Infrastructure), and 17 (Partnerships for the Goals). The project aims to deepen the university's commitment to regional social and environmental challenges, fostering a systemic approach to the university’s role in addressing community issues through research and outreach.